INTERNALISASI NILAI-NILAI PENDIDIKAN ISLAM PADA TRADISI ‘REMO’ DI DESA BANMALENG PULAU GILI RAJA SUMENEP - Moh. Musyfiq Sulaiman; Muliatul Maghfiroh; Mohamad Aso Samsudin (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2025)
Research and studies around the value of Islamic education are very much carried out. Likewise, research and study of certain cultures and traditions that take place in a certain area. Specific research and studies on the tradition of 'remo' or 'remoh' by Madurese people have also been carried out, both carried out by the Madurese people in various parts of the region and islands in Madura or by Madura communities outside Madura such as in Java, Kalimantan, and others. From the research and studies, it was found that there were doubts, biases, and inconsistencies in the values of Islamic education that were used as a perspective by the authors, even though the 'remo' tradition that was studied had many positive values that should be known by the public and maintained as a very valuable identity. Therefore, this research is focused on the reconceptualization of Islamic educational values based on the genealogy of thought that develops over time, and the 'remo' tradition based on the values of Islamic education. To reveal this, qualitative research was used using interview, documentation, and observation techniques on the literature on the value of Islamic education and the dimensions of Islam itself as well as real practices about the 'remo' tradition that took place in the village of Banmaleng, Giliraja, Sumenep. This research shows that: First, the classification of Islamic educational values is genealogical in the study of the Islamic dimension which is said to be Syaltut and Khallaf which in recent times has experienced a disconnection in the chain of development studies so that the Islamic educational values that have been widely circulated lately seem to jump from the Islamic dimension that has been introduced by previous experts; Second, there are nine values of Islamic education in the 'remo' tradition and are dominated by values with a moral dimension between fellow citizens.